Social disparities in the use of colonoscopy by primary care physicians in Ontario - Jacob, Binu J (BioMed Central, 2011)
BACKGROUND: It is unclear if all persons in Ontario have equal access to colonoscopy. This research was designed to describe long-term trends in the use of colonoscopy by primary care physicians (PCPs) in Ontario, and to determine whether PCP characteristics influence the use of colonoscopy. METHODS: We conducted a population-based retrospective study of PCPs in Ontario between the years 1996-2005. Using administrative data we identified a screen-eligible group of patients aged 50-74 years in Ontario. These patients were linked to the PCP who provided the most continuous care to them during each year. We determined the use of any colonoscopy among these patients. We calculated the rate of colonoscopy for each PCP as the number of patients undergoing colonoscopies per 100 screen eligible patients. Negative binomial regression was used to identify factors associated with the rate of colonoscopy, using generalized estimating equations to account for clustering of patients within PCPs. RESULTS: Between 7,955 and 8,419 PCPs in Ontario per year (median age 43 years) had at least 10 eligible patients in their practices. The use of colonoscopy by PCPs increased sharply in Ontario during the study period, from a median rate of 1.51 [inter quartile range (IQR) 0.57-2.62] per 100 screen eligible patients in 1996 to 4.71 (IQR 2.70-7.53) in 2005. There was substantial variation between PCPs in their use of colonoscopy. PCPs who were Canadian medical graduates and with more years of experience were more likely to use colonoscopy after adjusting for their patient characteristics. PCPs were more likely to use colonoscopy if their patient populations were predominantly women, older, had more illnesses, and if their patients resided in less marginalized neighborhoods (lower unemployment, fewer immigrants, higher income, higher education, and higher English/French fluency). CONCLUSIONS: There is substantial variation in the use of colonoscopy by PCPs, and this variation has increased as the overall use of colonoscopy increased over time. PCPs whose patients were more marginalized were less likely to use colonoscopy, suggesting that there are inequities in access.